Picomolar scale determination of carbohydrates covalently immobilized on activated beads using hydroxyl functionality - Yu, J; Chun, SM; Park, H; Park, YK; Jeong, S (SPRINGER SINGAPORE PTE LTD, 1999)
Since carbohydrates are major mediators in cell-to-cell adhesion and communication, the development of specific and strong binders against them could generate promising therapeutics. As the first step towards that goal, sugar molecules have to be immobilized to be used as an affinity matrix. The amino functionality in sugar is the most active nucleophile for the immobilization, if the amino group is available. An alternative and general method is to use the hydroxyl group as a direct nucleophile, but the quantitation of immobilized hydroxyl groups is not easily done. To overcome this limitation, we have developed a method to immobilize various isomers of monosaccharides with p-nitrophenyl groups to the beads by using their hydroxyl groups. It was found that the amount of immobilized sugar was independent of the structure of the sugar, but was dependent on the number of hydroxyl groups. We also developed a sensitive method to quantify the amount of immobilized sugar at the picomolar scale by utilizing commercially available glycosidases to release a sensitive reporter molecule, p-nitrophenol, and detect it by HPLC. This new technique would allow a facile quantitation method for immobilized sugar molecules, which could be used as the affinity matrix to develop strong binders against biologically important sugars.